Prolonged Toxicokinetics and Toxicodynamics of Paraquat in Mouse Brain - Prasad, Kavita (National Institute of Environmental Health Sciences, 2007)
BACKGROUND: Paraquat (PQ) has been implicated as a risk factor for the Parkinson disease phenotype (PDP) in humans and mice using epidemiologic or experimental approaches. The toxicokinetics (TK) and toxicodynamics (TD) of PQ in the brain are not well understood. OBJECTIVES: The TK and TD of PQ in brain were measured after single or repeated doses. METHODS: Brain regions were analyzed for PQ levels, amount of lipid peroxidation, and functional activity of the 20S proteasome. RESULTS: Paraquat (10 mg/kg, ip) was found to be persistent in mouse ventral midbrain (VM) with an apparent half-life of approximately 28 days and was cumulative with a linear pattern between one and five doses. PQ was also absorbed orally with a concentration in brain rising linearly after single doses between 10 and 50 mg/kg. The level of tissue lipid peroxides (LPO) was differentially elevated in three regions, being highest in VM, lower in striatum (STR), and least in frontal cortex (FCtx), with the earliest significant elevation detected at 1 day. An elevated level of LPO was still present in VM after 28 days. Despite the cumulative tissue levels of PQ after one, three, and five doses, the level of LPO was not further increased. The activity of the 20S proteasome in the striatum was altered after a single dose and reduced after five doses. CONCLUSIONS: These data have implications for PQ as a risk factor in humans and in rodent models of the PDP.